The role of emotion regulation in the experience of menstrual symptoms and perceived control over anxiety related events across the menstrual cycle - Manikandan, Sanjana (Arch Womens Ment Health, 2016)
PURPOSE: Hormonal variation throughout the menstrual cycle is posited to impact various physical and mental health symptoms; however, this is not observed in all women and mechanisms are not well understood. Difficulty in emotion regulation may elucidate differences women experience in physical and mental health functioning between menstrual phases. We examined the moderating role of difficulty in emotion regulation in the relation between menstrual phase and menstrual symptom severity and perceived control over anxiety-related events in healthy, regularly menstruating women. METHOD: The participants were 37 women (M(age) = 26.5, SD = 9.6). A series of regression analyses were used to examine whether individual differences in emotion regulation difficulties moderate the relation between menstrual phase and our outcomes, severity of menstrual symptoms and perceived control over anxiety related events, using a within-subjects design. RESULTS: The analyses revealed that difficulty in emotion regulation significantly moderated the relation between menstrual phase and perceived control over anxiety-related events (B = −0.42, p < .05), but not menstrual symptom severity. CONCLUSION: Women who reported higher emotion regulation difficulty experienced greater differences in perceived control over anxiety-related events between menstrual phases. Specifically, women lower in difficulty in emotion regulation report greater increase in control over anxiety during the late luteal phase compared to women with higher emotion regulation difficulty. Difficulty in emotion regulation may play an important role in understanding differences in menstrual phase-associated impairments, thereby informing the development of targeted interventions for vulnerable women.